Peran Rumah Subsidi dalam Meningkatkan Akses Hunian dan Perekonomian Masyarakat Berpenghasilan Rendah di Indonesia: Studi Kasus Kecamatan Sokaraja Kabupaten Banyumas - Tripustikasari, Eka (International Forum of Researchers and Lecturers, 2026)
Limited access to adequate housing remains a major challenge for low-income households in Indonesia, including in Banyumas Regency. The subsidized housing program has been implemented as a public policy instrument to improve housing affordability while enhancing social and economic welfare. This study aims to analyze the role of subsidized housing in improving housing access and the economic conditions of low-income communities in Banyumas Regency. The research adopts a qualitative approach using a documentation study method by collecting and analyzing policy documents, official government reports, scholarly journal articles, and relevant publications related to subsidized housing and the socio-economic conditions of low-income households. Data analysis was conducted through content analysis to interpret the role of subsidized housing based on indicators of housing affordability and household economic impacts. The findings indicate that subsidized housing significantly reduces the housing cost burden of low-income households from levels exceeding the affordability threshold to a more economically manageable range. The reduction in housing expenditure contributes positively to household economic stability by allowing savings and reallocation of income toward productive needs such as education, healthcare, and financial security. However, the effectiveness of subsidized housing in improving economic outcomes is still influenced by location and accessibility of housing areas. This study concludes that subsidized housing plays a crucial role in expanding housing access and improving the economic conditions of low-income communities, while requiring integrated and sustainable policy support to maximize its long-term benefits.